Răspuns :
a. = ( x - 1 ) ² - 5 ² = ( x -1 -5 ) · ( x -1 + 5) = ( x -6 ) · ( x + 4)
b. = ( x -2 ) ² - 5² = ( x -2 - 5) · ( x -2 + 5) = ( x - 7 ) · ( x + 3)
b. = ( x -2 ) ² - 5² = ( x -2 - 5) · ( x -2 + 5) = ( x - 7 ) · ( x + 3)
Avem formula [tex]a^2-b^2=(a+b)(a-b)[/tex]
Deci o putem aplica pentru expresia data:
[tex](x-1)^2-25=(x-1)^2-5^2=[(x-1)-5][(x-1)+5]= \\ =(x-6)(x+4)[/tex]
Pentru a doua expresie avem
[tex][(x-2)-5][(x-2)+5]=(x-7)(x+3)[/tex]
Deci o putem aplica pentru expresia data:
[tex](x-1)^2-25=(x-1)^2-5^2=[(x-1)-5][(x-1)+5]= \\ =(x-6)(x+4)[/tex]
Pentru a doua expresie avem
[tex][(x-2)-5][(x-2)+5]=(x-7)(x+3)[/tex]